Caso ARP Nº 18 - Correia, David Campos (2021)
72-year-old male, referred to our hospital due to 5-month history of dry cough, increasing abdominal discomfort and feeling of abdominal fullness. Laboratory results revealed anaemia, mild leucocitosis and elevated C-reactive protein levels. Ultrasound was initially performed, followed by Computed Tomography.